LEGAL PROTECTION OF VULNERABLE GROUPS OF POPULATION:: PRACTICE OF THE EUROPEAN COURT OF HUMAN RIGHTS - Matvieieva, Liliia; Baltadzhy, Polina; Shmalenko, Iuliia; Yeftieni, Natalia; Ivanchenko, Olga (Revista Gênero e Interdisciplinaridade, 2021)
The relevance of the problem under study is due to the need to monitoring the general situation to respect to human rights. The establishment, provision and realization of human rights is an important indicator in a state, which indicates its democracy, sociality, as well as the fact that such a state is legal. Purpose of the article in the study the issues of legal protection of vulnerable categories of population in the context of formation of active human rights policy of state aimed at increasing the capacity of socially vulnerable groups and reducing the risks of growing social tensions in society. The leading method for studying this problem is the legal sociological method, which allows us to study the effectiveness of state and legal regulation of human rights protection. The article presents an analysis of the results of the European experience in combating intolerance and discrimination. Its types main determined have been. Highlighted the criteria by which discrimination is prohibited. The legal system of human rights protection mechanisms is analyzed. The article presents scientific categories: discrimination, hate crimes, vulnerable groups. The practical significance lies in the development of proposals for improving domestic legislation.